The relationship between work life balance and organizational commitment among staffs in Jabatan Kemajuan Masyarakat (KEMAS) at Ayer Keroh, Malacca / Norfarhanah Ab Aziz - Ab Aziz, Norfarhanah (Faculty of Business and Management, 2013)
Nowadays, the elements in the work life balances have the potential significant to generate organizational commitment. It has a potential to improve employee morale, reduce absenteeism and improved employee commitment and productivity. Besides that, in work life balance gives awareness to the employee to gain objective and achieve goal of the organization. There are four elements that consist in work life balance which is telecommuting, maternity leave, flextime and childcare. Organizational commitment have a positive impact towards the employees' retention intention. In order to build high commitment among the employees it is very essential for them to feel belong on the organization. On the other hand, while there was no work lite balance was apply in the organization, it will decrcased the employee job satisfaction, indirectly it will increased the stafftumover, absenteeism, lower perfolmance, job stress level and intention to leave the organization. There are three elements of organizational commitment which is effective commitment, continuance commitment and nonnative commitment. Therefore, this study is to can)' out the relationship between work life balance toward organization commitment at Jabatan Kemajuan Masyarakat (KEMAS), Ayer Keroh, Melaka. In order to identify the relationship between these variables, 100 sets of questionnaire has been distributed among staffs at this organization.